Comparison of the Accreditation Status of Energy and Environment Laboratories in Brazilian, Austrian, German, and Swiss Universities - Nascimento, Diego [UNESP]; da Silva, Gustavo Henrique Romeu [UNESP]; de Lacerda Pereira, Gustavo Rorato Tonizza [UNESP]; Mathias, Mauro Hugo [UNESP] (My University, 2025)
This article offers a comprehensive analysis of the implications of ISO/IEC 17025 accreditation for university laboratories operating within the energy and environmental sectors. Through bibliographical research, database development and generation of comparative indicators, it was possible to identify the current scenario, resulting in a quantitative analysis. The research had a scope comparing Brazil with Austria, Germany, and Switzerland, countries in Europe characterized by a shared cultural similarity. Brazil leads with the largest number of laboratories in energy and environment sector; however, Austria is the country with the highest proportion of university laboratories when compared to the total number of laboratories. Furthermore, it was possible to verify that this standard accredits laboratories to participate in numerous projects, boosting the number of scientific projects and research.
Keywords: energy and environment sector; engineering university laboratories; ISO/IEC 17025; laboratory accreditation